Progressive Ovarian Cancer with Trocar Site Metastases Resulted from Inadequate Laparoscopy - Damayanti, Ina (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: Discuss the complications of laparoscopic ovarian cystic neoplasms. Method: Case report. A-52 year old female with 2 parities, complained of a lump at anterior abdominal wall during chemotherapy for clear cell ovarian adenocarcinoma after total hysterectomy and bilateral salphingooophorectomy by laparoscopy. The indication was suspected ovarian cancer from solid parts found during ultrasound and CA125 level 169. During previous laparoscopy, the cyst was ruptured, left in abdominal cavity with high CO2 pressure for five hours and retrieved without a bag. The frozen section examination of the cyst wall were diagnosed as endometriosis. The physician assured her that the lump was only scar and did not need further evaluation. CA125 level was 557 IU after chemotherapy. PET scan confirmed a 2 cm-diameter mass superior to peritoneum and multiple implants intra abdominally. Result: A debulking laparotomy was done. Omental cake was found with one part adhered to the right previous trocar insertion site. It was connected to tumor implant size 3x4 cm until fat tissue of abdomen wall. Another implant was also found at left paracolical area. Conclusion: Laparoscopy offers advantages such as less bleeding, better visualisation, and enhanced recovery. Some controversies exist in cases with suspicion of malignancy. Pneumoperitoneum might cause seeding of tumor cells. This could be prevented by using low pressure, avoidance of exsuflation of gas through trocar opening, or by using bags to retrieve operative specimens. Preoperative evaluation of clinical findings, ultrasound, and tumor markers are important to prevent improper surgical management. [Indones J Obstet Gynecol 2014; 2: 110-113] Keywords: complication, laparoscopy, metastases, ovarian cancer, trocar site.